2007
DOI: 10.1353/hsj.2007.0018
|View full text |Cite
|
Sign up to set email alerts
|

High School Department Chairs - Perspectives on Instructional Supervision

Abstract: A case study approach was used to examine the perspectives of three high school department chairs and their work at providing instructional supervision to the teachers in their departments: math, science, and social studies. We sought to discover the beliefs and practices of three department chairs in one high school, located in a southeastern state. From interview data, three primary findings emerged: 1) The high school department chairs experienced role conflict and ambiguity relative to providing instructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 8 publications
4
30
0
Order By: Relevance
“…Secondary school department chairs are considered content-area specialists and instructional leaders who occupy organizational positions that lie between senior leadership and teachers (Feeney, 2009;Hannay & Erb, 1999;Lucas, 2000;Sergiovanni, 1984;Tucker, 1993;Wettersten, 1994;Zepeda, 2007). Their position, as Ginny Lee (1987) and Kenneth Leithwood (1994) observed, requires them to simultaneously manage the smooth operations of their departments while leading meaningful change Secondary School Department Chairs Leading Successful Change within them.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary school department chairs are considered content-area specialists and instructional leaders who occupy organizational positions that lie between senior leadership and teachers (Feeney, 2009;Hannay & Erb, 1999;Lucas, 2000;Sergiovanni, 1984;Tucker, 1993;Wettersten, 1994;Zepeda, 2007). Their position, as Ginny Lee (1987) and Kenneth Leithwood (1994) observed, requires them to simultaneously manage the smooth operations of their departments while leading meaningful change Secondary School Department Chairs Leading Successful Change within them.…”
Section: Introductionmentioning
confidence: 99%
“…However, majority of HoDs lack significant skills and competences as leaders. In the literature, it is found that HoDs are not ready to lead (Turner, 2000), they learn during doing their job, and lack of time for planning and leading (Ali & Botha, 2006;Zepeda & Kruskamp, 2007;Rosenfeld et. al, 2009;Bak, 2010).…”
Section: Problem Statement Of the Studymentioning
confidence: 99%
“…Zepeda and Kruskamp (2007) conducted a study in the USA investigating the perceptions of HoDs about the provision of instructional supervision in their departments. It was found that HoDs were not prepared for the supervision role, they also lack support and guidance from the principals, and they faced role ambiguity in their assigned position, and role tension.…”
Section: Hods Instructional Supervisionmentioning
confidence: 99%
“…In Korea, Sook, and Ju (1997:113) have analyzed of the reality of educational Supervision in Korea, explained the obstacles facing the system of educational supervision, and recommended a change in the policies of supervision, and development of the performance of Supervisors. In Turkey, Oglu, et al (2007:128) have recommended the need to restructure the system of educational Supervision in Turkey, and to commensurate the educational regulations and policies at Turkish Ministry of Education .In the United States of America (Sandra, 2001;Zepeda andKruskamp, 2007 andGlanz, 2008) have studied the Supervisory work, and stressed that the supervision need further improvement and development. It can be argued that educational supervision can fulfill many educational goals so the current study tries to identify the reality and the importance of managers' practices on the educational supervision process for evaluation at the departments of education in the kingdom of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%